Effect of Experimental Coronary Thrombosis upon Platelet Kinetics - Moschos, Christos B.; Lahiri, Kamalesh; Manskopf, Gisbert; Oldewurtel, Henry A.; Regan, Timothy J. (Thrombosis and Haemostasis, 1973)
A study was designed to determine the effect of experimental coronary thrombosis upon quantitative changes of platelets in the coronary sinus blood and in the systemic circulation. In addition, using 51Cr-labelled platelets, their distribution in the organ primarily affected by the presence of thrombus, namely the heart, and organs known to be involved in platelet kinetics such as liver, spleen and lungs, was also examined. Following coronary occlusion, a consistent pattern of progressive decrease in platelet counts in the effluent of the infarcted area (coronary sinus) as well as in the systemic blood, maintained for at least 18-20 hours following the thrombotic event, was observed. There was a significant increase in platelet sequestration by spleen, liver and lung and presence of platelet thrombi in the microcirculation of the coronary arterial system. The results suggest that a thrombotic process in a medium size artery induces a more generalized involvement of the platelet population through mechanisms which are not clear at this time. The changes in platelet counts, following coronary thrombosis, obtained as described in this study offer diagnostic possibilities in cases where an active thrombotic process is suspected. However, further studies are necessary before the value of this diagnostic approach is established.